RELATIONSHIP BETWEEN STRESS AND ACADEMIC PERFORMANCE AMONG STUDENTS IN FKIK UKRIDA CLASS OF 2017-2019 DURING COVID-19 PANDEMIC - Dreimahlon Tumonggor; Yosephin Sri Sutanti; Evan Evan; Susanty Dewi Winata (Dinasti International Journal of Education Management And Social Science, 2021)
Stress is very common among medical students especially during the Covid-19 pandemic, this may reduce academic performance and cause harm to the patient's care in the future. The purpose of this study was to determine the relationship between stress and academic performance. This type of research is non-experimental analytic observational with a cross-sectional approach. The sample of this research was 146 students of Krida Wacana Christian University Faculty of Medicine and Health Sciences (FKIK Ukrida) class 2017-2019. The sampling technique is probability sampling with a stratified random sampling type. The instrument used in this study was perceived stress scale-10 (PSS-10) questionnaire. The data analysis was carried out using spearman rank test. The results showed that the value of p = 0.001 (<0.005) with a correlation value of 0.260, which means that there is a relationship between stress and academic performance of FKIK Ukrida students class 2017-2019 during the Covid-19 pandemic.